PENDELEGASIAN WEWENANG DALAM MENEGAKAN PERATURAN DAERAH NOMOR 4 TAHUN 2013 TENTANG PELARANGAN PEREDARAN DAN PENJUALAN MINUMAN BERALKOHOL DI KOTA CIREBON (STUDI KASUS SATUAN POLISI PAMONG PRAJA KOTA CIREBON) - Mey Luvita; Rahmat Hidayat; Iskandar Zulkarnaen (Jurnal Ilmiah Publika, 2017)
ABSTRACTDelegation of authority is a right or power of the leadership of subordinates to carry out her duties and requested accountability for the completion of these tasks Civil Service Police Unit is the local technical institute, who are the delegates as enforcement of local regulations No. 4 of 2013 on the prohibition of the distribution and sale of alcoholic beverages in the city of Cirebon. Some problems in the implementation of delegation of authority is still their circulation and sale of alcoholic beverages from class A to class c well supplied and sold in karaoke entertainment venues, cafes, shops and agents.In this study the author uses the theory of the Delegation of Authority proposed by Manullang in his book entitled "Management Basics" (2008: 205), which states that "management is achieving results through others, therefore to be able to realize the manager delegates the absolute need. One of the important qualification of a manager is the ability to delegate some of the tasks and authority to his subordinates. "In this study, the authors used a qualitative method with descriptive analysis and interview with the informant as a source of information”.The results of this research that the Civil Service Police Unit has a very important role as delegates in combating the distribution and sale of alcoholic beverages in the city of Cirebon. But in reality, delegation of authority implemented still not optimal. Still the distribution and sale of alcoholic beverages due to the performance of civil service police unit that is not optimal, among others, is due to less effective and maximum pelaksaanan duties, authority and accountability, lack of budget, personnel and motivation in enforcing local regulations No. 4 of 2013 on banning and sale of alcoholic beverages in the city of Cirebon.